Evaluating Pain and Analgesia Effectiveness Following Routine Castration in Rabbits Using Behavior and Facial Expressions - Miller, Amy L.; Clarkson, Jasmine M.; Quigley, Caroline; Neville, Vikki; Krall, Caroline; Geijer-Simpson, Annika; Flecknell, Paul A.; Leach, Matthew C. (Frontiers in Veterinary Science, 2022)
Prevention of pain in rabbits is a priority for both welfare and validity of scientific data. We aimed to determine if the rabbit grimace scale (RbtGS) could be used as a viable, rapid assessment tool in two breeds of rabbit, Dutch belted (DB) and New Zealand white (NZW), following orchidectomy, as an adjunct to behavioural analysis. All animals received analgesia. Rabbits were filmed and their behaviour was recorded at multiple time points pre- and post-orchidectomy. Observers then scored specific pain associated behaviours for analysis. Time matched footage was also scored using the rabbit grimace scale (RbtGS). Following surgery, rabbits showed significant increases in the duration spent displaying key pain associated behaviours at 1 and 5-hours post-surgery. DB rabbits that received meloxicam showed significantly more pain behaviours at 1 and 5-hours post-surgery compared to those administered a combination of meloxicam and a lidocaine/bupivacaine local infusion. DB rabbits showed an increase in RbtGS score at both 1- and 5-hours post-surgery. In the NZW rabbits, an increase in RbtGS score was only observed at 1-hour post-surgery. Using behavioural analysis as the gold standard for comparison, the RbtGS was an effective means of determining when rabbits are painful following orchidectomy. Multimodal analgesia was a more effective method of reducing pain, compared to meloxicam alone.